The digitally preserved old-aged art, culture and artists: An exploration of Google Arts and Culture. Issue 2 (2nd August 2019) - Wani, Showkat Ahmad; Ali, Asifa; Ganaie, Shabir Ahmad
Abstract : Purpose: This paper aims to explore the Google Arts and Culture platform in terms of parameters used for categorizing the digital collections by it; the total number of items and their types; top contributing artists; top ten historical events and figures; and the top ten countries having maximum artworks. Design/methodology/approach: An online method was used to collect the relevant data for achieving the objectives of the study. Data were harvested from the official website of Google Arts and Culture (https://artsandculture.google.com/ ) during the period of 15 May to 31 May 2018, and the same was tabulated in MS Excel for analysis and interpretation. Findings: The findings revealed that Google Arts and Culture includes a total of 6, 272 artists, 228 media and 121 art movements. Moreover, there are a total of 641 historical movements; 6, 250 historical figures; 9, 692 places; 3, 226 museum views; 1, 702 zoom views; 39, 607 featured videos; and 5, 528 featured stories; 122 items organized by color and 954 organized by time. Originality/value: The present study is first of its kind that focuses on exploration of diverse arts and cultural heritages of different countries and by diverse artists made visible by Google Arts and Culture initiative. It will significantly reinforce the art and cultural heritage lovers to acquire the knowledge pertinent to various types of arts and cultures that prevailed in antiquity across the globe and also make aware the conservators about how to use digital technologies for efficient preservation and visibility of unique artworks, artists and the places whom they belong.